2020
DOI: 10.1002/jcop.22403
|View full text |Cite
|
Sign up to set email alerts
|

Social support as a mediator of occupational stressors and mental health outcomes in first responders

Abstract: This cross‐sectional study aimed to address whether occupational stressors are associated with adverse mental health outcomes in first responders via lower social support. A total of 895 first responders including emergency medical technicians, paramedics, and firefighters from 50 US States and the Virgin Islands (mean = 37.32, standard deviation = 12.09, 59.2% male, and 91.3% White) completed an online survey. Bivariate analyses indicated that occupational stressors were positively correlated with posttraumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The 95% bias-corrected bootstrap confidence interval (CI) and 95% percentile CI based on 3000 bootstrap samples were used for testing the mediating effects. All the indices and mediating effects were determined when zero was not included in the respective CI [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The 95% bias-corrected bootstrap confidence interval (CI) and 95% percentile CI based on 3000 bootstrap samples were used for testing the mediating effects. All the indices and mediating effects were determined when zero was not included in the respective CI [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…While biomarkers of resilience have not yet been thoroughly studied, there is a large amount of evidence for psychological protective factors of resilience, which has been highly associated with environmental factors (18)(19)(20). Some protective factors early in life include self-regulation, family support, school support, and peer support (18), while social support and self-care (i.e., exercise, sleep, and work-life balance) are highly important throughout the entire life (19,20). Major psychological therapies and resilience training incorporated in the past that have had a positive effect on individual resilience include cognitive therapy and mindfulness training.…”
Section: Introductionmentioning
confidence: 99%
“…Prior finding suggested that social support is not only related to objective occupational stressors, but also related to individual perceived stress ( Kneavel, 2021 ). Occupational stressors are work-related factors, which are objective factors that cause stress in one’s job ( Kshtriya et al, 2020 ), perceived stress is the psychological response to threatening stimuli in the environment after cognitive evaluation ( Li and Lyu, 2020 ). It is crucial to distinguish the buffering effect of social support on occupational stressors and perceived stress.…”
Section: Introductionmentioning
confidence: 99%